Limited ventilation of the central Baltic Sea due to elevated oxygen consumption - Naumov, Lev; Neumann, Thomas; Radtke, Hagen; Meier, H. E. Markus (Frontiers in Marine Science, 2023)
The Baltic Sea is known as the world’s largest marine system suffering from accelerating, man-made hypoxia. Notably, despite the nutrient load reduction policy adopted in the 1980s, the oxygen conditions of the Baltic Sea’s deep waters are still worsening. This study disentangles oxygen and hydrogen sulfide sources and sinks using the results from the 3-dimensional coupled MOM-ERGOM numerical model and investigates ventilation of the deep central Baltic Sea by the 29 biggest oxygen inflows from 1948 to 2018 utilizing the element tagging technic. Everywhere across the central Baltic Sea, except in the Bornholm Basin, a shift in oxygen consumption from sediments to water column and a significant positive trend in hydrogen sulfide content were observed. The most notable changes happened in the northern and western Gotland basins. Mineralization of organic matter, both in the water column and sediments, was identified as the primary driver of the observed changes. A significant negative trend in the lifetime of inflowing oxygen was found everywhere in the central Baltic Sea. It leads to the reduced efficiency of natural ventilation of the central Baltic Sea via the saltwater inflows, especially in the northern and western Gotland basins.